Use of Laser Speckle Contrast Analysis during pelvic surgery in a uterine transplantation model - Saso,S; Tziraki,M; Clancy,NT; Song,L; Bracewell-Milnes,T; Jones,BP; Al-Memar,M; Yazbek,J; Thum,M-Y; Sayasneh,A; Bourne,T; Smith,JR; et al. (Future Science OA, 2018)
Aim: Uterine transplantation (UTx) is proposed for treatment of uterine factor infertility. Our aim was to assess whether Endoscopic Laser Speckle Contrast Analysis (eLASCA) could evaluate pelvic blood flow at anastomotic sites required for sheep and rabbit UTx. Results/methodology: eLASCA detected blood flow in rabbit UTx #7 and #9. In sheep UTx #2, #3 and #5, the results allowed us to conclude that blood flow was present in the uterine graft following transplantation; and post-UTx, the animal had heart and respiratory rates, and oxygen saturation compatible with a normal hemodynamic status. Conclusion: These preliminary results establish the potential of Laser Speckle Contrast Analysis as noncontact and real-time tool for observation of spatially-resolved blood flow from which other parameters can be derived.